Process for obtaining medium chain triacyglycerols containing oryzanol from deodorizer distillates for the use in sunscreen formulation. - Lai, Oi Ming; Lo, Seong Koon; Kong, Ching; Low, Chee Tein (2003)

(untitled)
Lipase catalyzed esterification reaction producing medium chain triacyglycerols (MCTs) in which involves esterifying some or all the medium chain fatty acids from mixture of deodorizer distillates with glycerol. Separation step is performed to obtain MCTs and to be included into a sunscreen formulation together with y-oryzanol and anti-oxidants.